2020
DOI: 10.21037/atm.2020.04.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 60 discharged cases of 2019 novel coronavirus-infected pneumonia in Taizhou, China

Abstract: Background: The number of patients with pneumonia stemming from the 2019 novel coronavirus (COVID-19) infection has increased rapidly. However, the clinical characteristics of discharged patients remain little known. Here, we attempt to describe the clinical characteristics and treatment experiences of discharged cases from Taizhou, China.Methods: A total of 60 patients with COVID-19-infected pneumonia who were discharged from Taizhou

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…In addition, hospitals in Wuhan only accept patients who have been diagnosed as showing COVID-19, while hospitals outside Wuhan admitted many patients who were not diagnosed at admission and were also hospitalized for the 1-3 days it took for nucleic acid test results to arrive. Three studies from regions with sufficient medical resources [32][33][34], namely Taizhou, Guangdong, and Shenzhen, can support our hypotheses since their median hospital stays were 18 days, 20 days, and 20 days, respectively, which were close to the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, hospitals in Wuhan only accept patients who have been diagnosed as showing COVID-19, while hospitals outside Wuhan admitted many patients who were not diagnosed at admission and were also hospitalized for the 1-3 days it took for nucleic acid test results to arrive. Three studies from regions with sufficient medical resources [32][33][34], namely Taizhou, Guangdong, and Shenzhen, can support our hypotheses since their median hospital stays were 18 days, 20 days, and 20 days, respectively, which were close to the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Then, 771 articles were removed after reading the title and abstract, and 142 were excluded from the remaining 319 articles for various reasons. In the end, 55 full-text studies involving 10014 COVID-19 patients were included in this meta-analysis based on the detailed assessment and inclusion criteria (Figure 1) [20,21,22,23,24,25,26,27,28,29,30], [31,32,33,34,35,36,37,38,39,40], [41,42,43,44,45,46,47,48,49,50] also found that most of these studies (n ¼ 49) were based in China, although three studies were identified from the USA, two studies were from Italy, and one study from South Korea was included. The quality of most included studies was of high quality (score ranges between 6-8) assessed by the Newcastle Ottawa scale.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Fever, cough, fatigue, anorexia, myalgia, dyspnea, chest tightness, sputum production, hemoptysis, pharyngalgia, diarrhea, nausea, vomiting, abdominal pain, headache, dizziness and sore throat were reported in 47,46,37,8,34,40,22,25,4,7,39,17,18,9,27, 10 and 13 studies, respectively. The percentages of these symptoms in severe and nonsevere COVID-19 cases are presented in Figure 3 and Table 2, and forest plots are presented in Figure 9.…”
Section: Effect Of Clinical Symptoms On the Disease Severitymentioning
confidence: 99%
“…Patients with this disease commonly present with symptoms like fever, fatigue, dry cough, sore throat, and difficulty breathing [ 2 ]. A number of patients may also develop lymphopenia and pneumonia with characteristic findings on chest computed tomography (CT) [ 3 ]. Several clinical studies have identified comorbidities like hypertension, diabetes mellitus, chronic obstructive pulmonary disease, cardiovascular disease, and obesity as risk factors for worsening of outcomes with COVID-19 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%